Persepsi Nasabah Tentang Pembiayaan Murabahah dan Implikasinya Terhadap Minat Beli Bank Syariah Indonesia KCP Jombang - Widyaningsih, Bekti; Ayuningtiyas, Eka (Universitas KH. A. Wahab Hasbullah, 2022)
This study explores a customer's perception of the implications of murabahah financing on buying interest at Bank Syariah Indonesia KC Jombang. This study aims to describe customer perceptions of the attractiveness of murabahah financing at Bank Syariah Indonesia KC Jombang, explain customer buying interest in murabahah financing at Bank Syariah Indonesia KC Jombang, explain the implications of perceptions of customer attractiveness on interest in buying murabahah financing products at Bank Syariah Indonesia KC. Jombang viewed from the theory of Consumer Behavior (Consumer Behavior. The research analysis used is a qualitative case study approach which is a strategy or method that is powerful enough to examine in depth the case to be studied. The study concluded that customer perceptions related to murabahah financing has several attractions, interest in buying murabahah financing at Indonesian Sharia Bank KC Jombang is quite high due to several internal and external factors, while the implications of customer perceptions of Sharia Bank KC Jombang are viewed from the theory of Consumer Behavior ( Consumer Behavior) related to murabahah financing can generate customer buying interest without any hesitation in deciding to apply for financing.